Physical properties of dressing-type oil in water emulsions as affected by okra gum-xanthan gum-corn starch interactions - Nor Hayati Ibrahim,; Chang, Hon Weng (Penerbit Universiti Kebangsaan Malaysia, 2017)
Okra gum is one of potential hydrocolloids due to its’ suspending and emulsifying abilities and blending it with other gums shall widen its application in emulsion-based food products. Therefore, interaction effects of okra gum (OG), xanthan gum (XG) and corn starch (CS) on the physical properties of dressing-type emulsions were investigated in this study using a simplex-centroid mixture design. Application of OG:CS blend resulted in smaller droplet size range (5.40 – 11.22 μm) compared to XG:CS (4.82 – 13.97 μm) with the same gum ratio (i.e. 1:1), due to emulsifying property of OG. Emulsion prepared with this blend also exhibited better viscosity (30.43 ± 9.81 Pa.s) and turbidity (Absorbance value = 0.95 ± 0.12) compared to other emulsions with individual OG or CS. Regression modelling further confirmed the occurrence of synergistic interaction in OG:CS blend which positively affected these emulsion properties. Droplet size and turbidity responses were successfully fitted with a special cubic model while viscosity response was successfully fitted with quadratic model (no lackof- fit, p > 0.05). The models are useful for predicting the respective responses to any blend combination of the components. Results of this study signify that OG is a promising hydrocolloid showing synergism with CS and this synergism can be manipulated to overcome lack of OG performance in food emulsion.